Analysis of snowboarding performance at the Burton open Australian half-pipe championships - Harding, J. W.; James, D. A. (International Journal of Performance Analysis in Sport, 2010)
Half-pipe snowboarding performance is assessed by subjective measures. Knowledge of the relative importance of objective performance indicators however can improve training and competition performance assessment. We analysed previously developed key performance indicators at the Burton Open Australian Half-Pipe Championships over three years (2006, 2007, 2008). Linear regression showed the two individual key performance indicators most strongly correlated to competition success and multiple linear regression (enter method) showed the shared variance in scores explained by these objective variables. The two objective performance variables most highly correlated with competition success were average air time (AAT) and average degree of rotation (ADR). When combined (multiple linear regression), AAT and ADR objectively explain 71 - 94% of shared variance in subjective competition scores. We compared magnitudes of differences in AAT and ADR between athletes achieving top three (podium) final rankings and those achieving final rankings outside the top three. Magnitude of difference between athletic performances was established with a standardised (Cohen's) effect size (ES) with 95% confidence limits. Differences in AAT and ADR between athletes placing in the top three and those finishing outside the top three routinely showed moderate (ES = 0.6 - 1.2 95% CL) to very large (ES >2.0 95% CL) effects.